Prevalence and Clinical Correlates of Sarcopenia, Identified According to the EWGSOP Definition and Diagnostic Algorithm, in Hospitalized Older People: The GLISTEN Study - Bianchi, Lara; Abete, Pasquale; Bellelli, Giuseppe; Bo, Mario; Cherubini, Antonio; Corica, Francesco; Di Bari, Mauro; Maggio, Marcello; Manca, Giovanna Maria; Rizzo, Maria Rosaria; Rossi, Andrea P; Landi, Francesco; et al. (The journals of gerontology. Series A, Biological sciences and medical sciences, 2017)
Prevalence of sarcopenia is substantial in most geriatrics settings, but estimates vary greatly across studies because of difference in population characteristics, diagnostic criteria, and methods used to assess muscle mass, muscle strength, and physical performance. We investigated the feasibility of the European Working Group on Sarcopenia in Older People (EWGSOP) algorithm assessment in hospitalized older adults and analyzed prevalence and clinical correlates of sarcopenia. Cross-sectional analysis of 655 participants enrolled in a multicenter observational study of older adults admitted to 12 acute hospital wards in Italy. Sarcopenia was assessed as low skeletal mass index (kg/m2) plus either low handgrip strength or low walking speed (EWGSOP criteria). Skeletal muscle mass was estimated using bioimpedance analysis. Of the 655 patients (age 81.0 ± 6.8 years; women 51.9%) enrolled in the study, 275 (40.2%) were not able to perform the 4-m walking test because of medical problems. The overall prevalence of sarcopenia on hospital admission was 34.7% (95% confidence interval 28-37) and it steeply increased with aging (p < .001). In multivariable analysis, patients with sarcopenia on hospital admission were older and were more likely to be male and to have congestive heart failure, cerebrovascular disease, and severe basic activities of daily living disability. The prevalence of sarcopenia was inversely correlated with body mass index. Based on EWGSOP criteria, prevalence of sarcopenia is extremely high among older adults on admission to acute hospital wards. Older age, male gender, congestive heart failure, cerebrovascular disease, severe activities of daily living disability, and body mass index were the clinical variables significantly associated with the presence of sarcopenia.